The Relationship Between Self-Efficacy and Stress Levels Among Nursing Students Undergoing Clinical Practice For the First Time - Achmad Vindo Galaresa; Firmansyah; Habsyah Saparidah Agustina; Annisa Mazda Firdaus (Institut Citra Internasional, 2026)
Stress is a common problem frequently experienced by nursing students during clinical practice. Factors such as academic workload, adaptation to a new environment, and high academic expectations may increase the risk of stress. Self-efficacy is assumed to play an important role in reducing stress levels. This study aimed to investigate the relationship between self-efficacy and stress levels among students undertaking their first clinical practice at the Health Department of Subang State Polytechnic. This quantitative study employed a descriptive correlational design with a cross-sectional. The sample consisted of 120 third-semester students who were about to undertake clinical practice, selected using total sampling. The instruments used were the General Self-Efficacy Scale (GSES) and the Depression Anxiety Stress Scale (DASS-21). Data were analyzed using the Spearman Rank test. The results showed that 86% of students had high self-efficacy. The result showed that, 43.3% experienced moderate stress, 31.8% severe stress, 13.3% mild stress, and 11.6% were within the normal category. There was a significant negative relationship between self-efficacy and stress levels (r = -0.210; p = 0.040). Higher self-efficacy was associated with lower stress levels. Programs to enhance self-efficacy should be integrated with psychomotor skills training in nursing laboratories to better prepare students for clinical challenges and develop effective stress-management skills. This can be achieved by incorporating stress-management content into the curriculum, particularly in early programs and during students first clinical experiences.